Peningkatan Pengetahuan dan Keterampilan Kader Posyandu Melalui Pelatihan Antropometri Untuk Deteksi Dini Balita Stunting di Desa Jatisura, Indramayu - Nur Intania Sofianita; Iin Fatmawati; Sintha Fransiske Simanungkalit; Ikha Deviyanti Puspita; M. Ikhsan Amar (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Efforts to improve nutritional status for the development of human resources quality begin as early as possible, through 1000 HPK activities, starting from the fetal life to 2 years of age. One of the activities that support early detection of stunting under-fives is measurement and weighing which is carried out every month by health cadres at Posyandu. The purpose of implementing training for Posyandu cadres was to increase the knowledge and skills of Posyandu cadres in anthropometric measurements, and to minimize mis-weighing, measurement errors that make the data invalid and cannot be reported. The implementation method is by providing anthropometric training 1 time, filling out questionnaires before and after the training, by giving measurement tutorial for 120 minutes, and direct monitoring is carried out 1 month after the training. The result of this showed that there was increments of knowledge and measuring skills by Posyandu cadres (P value:0,006). Suggestions for the Posyandu cadres should have training and workshop for maintaining their skill, to be able to carry out anthropometric training regularly every year.